PENERAPAN FUZZY LOGIC DALAM PENENTUAN KELAYAKAN PEMBERIAN KREDIT - Saifulloh .; Wing Wahyu Winarno; Emha Taufiq Luthfi (Universitas Muhammadiyah Ponorogo, 2017)
Cooperatives provide financing assistance in the form of credit or installment payments and have multiple systems, procedures andrequirements to be met by the prospective customer. Nonetheless, there is the problem that many cases lending arrears return ofcredit. For this reason the study was conducted in an effort to develop a decision support system that can help the credit in taking adecision. This decision support system using Fuzzy Logic method application. This study will produce a prototype system whichfunctions which resulted in the decision creditworthiness and alternative decisions based on nominal submission. On the other handwith this system can also assist the cooperative in minimizing non-performing loans with an effort to provide loans based on thelowest value.